Lower-leg cooling during halftime does not affect second-half performance in a football match - Park, J.; Kim, D.; Park, J. (International Journal of Applied Sports Sciences, 2018)
Background: Cold application (e.g.,lower-leg cooling: LLC) during halftime is becoming more popular in football matches. Therefore, we examined the effects of a 5-min halftime LLC (7.5±1.0 ; bare feet immersed up to the tibial tuberosity), as a recovery strategy on subsequent performance changes in the second-half. Methods: Twenty male elite football players (age: 19±1 years; height: 176±6 cm; mass: 69±7 kg; athletic career: 9±1 years) participated in this crossover study (LLC or passive recovery: sitting on a bench without cooling). The 5-min FSP with a fixed intensity and distance, consisted of football-related activities (two trials of sprinting, jumping, dribbling, and kicking in various intensities and distances) and was repeated nine times (total 45-min) to mimic the first- and second-half of a football match. Calorie expenditure, heart rate, athletic performance, and passing accuracy were recorded. To determine feasibility, we compared our data to the normative values in previous reports. To test the condition effects over time, we performed a 2×6 mixed model analysis of variance for calorie expenditure and heart rate. For athletic performance and passing accuracy, we performed a 2×6 mixed model analysis of covariance (covariate: baseline measurement). Results: There were no statistical differences between the LLC condition and passive recovery on athletic performance and passing accuracy at any time point (p>0.13 for all statistical tests). Recorded calorie expenditure (1,227±142kcal) and heart rate (163±11bpm) during our FSP were within the normative values of a typical football match (calorie expenditure: 1,200to1,500kcal; heart rate: 150 and 175bpm). Conclusions: Since a 5-min halftime LLC (at 7.5) immersed up to the tibial tuberosity are not effective in delaying fatigue and passing accuracy, it is not recommended for a recovery strategy. Since simulated football matches using the FSP were similar to a typical football match in terms of calorie expenditure and heart rate, it could be used for future research or training purposes.